TaPUB15, a U‐Box E3 ubiquitin ligase gene from wheat, enhances salt tolerance in rice. (31st October 2020) - Li, Qiaoru; Li, Bo; Wang, Jingyi; Chang, Xiaoping; Mao, Xinguo; Jing, Ruilian
Abstract: Plant U‐box (PUB) E3 ubiquitin ligases play essential roles in response to environmental stresses and hormone signaling, but little is known about them in wheat ( Triticum aestivum L.). We characterized a U‐box E3 ubiquitin ligase gene, TaPUB15, which is conserved in wheat cultivars. TaPUB15 was expressed in multiple tissues, and the expression was much higher in roots than in other tissues. Transcription of TaPUB15 was induced by salt, abscisic acid, 4°C, and polyethylene glycol (PEG). Overexpression of TaPUB15‐D led to improve salt tolerance in transgenic rice, along with more roots in transgenic rice. Ion flux assays showed that transgenic rice plants had improved salt tolerance and maintained low Na + /K + ratios under salinity stress. Gene expression assays indicated that several salt stress‐related genes were significantly upregulated in transgenic rice relative to the wild type. These results from transgenic rice were also verified in transgenic Arabidopsis . Our data showed that TaPUB15 plays crucial roles in enhancing salt tolerance in crop plants and served a valuable gene resource for promoting the breeding of salt‐tolerant wheat in the future. Abstract : TaPUB15 might participate in regulation of salt stress pathways or networks to maintain a relatively low Na + /K + ratio to enhance salt tolerance in transgenics. In addition, TaPUB15 might promote water absorption by increasing root development in salt stress conditions, thereby enhancing salt tolerance. In a word, TaPUB15 could be a candidate gene to improve salt tolerance in crop breeding.